South China Sea maritime territorial disputes in COVID-19 Situation - Agrivina Vivian Giovanni; Fariz Pradipta Mursyid (Technium Social Sciences Journal, 2021)
The “nine-dash-line” claimed by China on the South China Sea has created a territory dispute that been remained unresolved for decades; instead it has emerged tension between China and the disputed countries, especially in South East Asia region. Each of these countries have their own strategic interests in the region, from natural resources, territorial claims to safeguarding freedom of navigation and sea lines of communication. The disputes itself attracting other countries outside South East Asia to join the arena by conducting several strategic moves towards the affected to gain their support against China. This paper will discuss about China and other affected actors’ efforts in claiming South China Sea as their territory, and examine possible background behind it, which also correlated to current situation developed in the arena especially during COVID-19 situations. Therefore, national interest concept will contribute to gain an understanding of the issue that could provoke international conflict